PENGHASILAN BIOPLASTIK OLEH ISOLAT INDIGENUS Bacillus sp. AMILOLITIK DENGAN SUBSTRAT PATI SUWEG (Amorphophallus campanulatus) - Margino, Sebastian; Sari, Rarat Mulat; Martani, Erni (Jurnal BioWallacea, 2015)
bioplastic that was synthesized by bacteria. Glucose as the main carbon source for PHBproduction but its cost was expensive, so we need to substitute with another substrate,including starch.The ability of amylolytic bacteria hydrolyzed starch into simple sugars andconverted to PHB can minimize the costs of PHB production. This research aim was to findout amylolitic bacterial isolates and produce PHB using the selected isolate. A total of 52bacteria were isolated using starch mediumfrom soil sample around Amorphophalluscampanulatus plant. Twenty eight among of them had amylase activity, and eleven among ofthem had amylase activity value equal or more than 2 point.The next selection was donebased on the specific amylase activity and found that five of those isolates had specificamylase activity more than 10 DUN/mg.Final selection was done based on PHB productionand found that isolate E5 had the high amylase activity and PHB production. PHB productionused isolate E5 in optimum conditions (inoculum concentration 10 %, elephant foot yamstarch 3 %, medium pH 7, temperature 30 Â°C, agitation 125 rpm, and 48 hour incubationtimeshowed that percentage of PHB increased from 9,5% to 14,5%. Characterization andidentification showed that isolate E5 closed to the genus Bacillus sp.Keywords : Amylolytic Bacillus sp., poly-Î²-hidroxybutyrate, elephant foot yam starch.